IMPLEMENTATION OF STUDENT DISCIPLINE CHARACTER VALUE AT SDN 161 PEKANBARU - Citra Novita Laura; Dea Mustika (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper reports the implementation of character values, obstacles, and solutions for students, which is conducted at SDN 161 Pekanbaru. The research uses a qualitative approach. Data collection techniques used in the research include interviews, observation, and documentation. The research uses documentation because researchers conducted observations and interviews. Data collection tools used by researchers are observation sheets, interviews, and documentation. The validity of the research material is checked by asking teachers and students about problem findings and further observations. The research results indicate that at SDN 161 Pekanbaru through the implementation of the character values of student discipline, time management discipline, the discipline of obeying school rules, discipline of behavior, and discipline of doing worship, which was achieved as expected student discipline character values.Â